Patani Scholars' Views on Tawassul with the Prophet and Righteous: Analysis of Abd al-Qadir bin Wangah's Risalah Irsyad Al-Jawiyīn - Isma-ie Katih (UIN Sunan Gunung Djati Bandung, 2023)
This study explores the theological concept of Tawassul in the Islamic tradition of the Nusantara region, focusing on Patani scholars' perspectives, particularly in Abd al-Qadir bin Haji Wangah Sela Budi Sekam Fatani's manuscript